Kesulitan Menyelesaikan Soal Cerita Matematika Pada Siswa Smp Negeri 1 Colomadu Tahun Pelajaran 2014/2015 - Khasanah, Ummi; , Prof. Dr. Sutama, M.Pd (2015)
The aims of this research is to describes the difficulties of students on aspects of language, prerequisites, and applied in problem solving of word math. This research is a descriptive qualitative ethnography design. The subjects of this research are students of SMP Negeri 1 Colomadu. The technique of collecting the data through observation, interview, and documentation. Research time in the second semester in 2014/2015 academic years. The validity of the data using triangulation of sources and methods. The techniques of analyzing the data consist of three-line activities. The results (1)the difficulties of the language aspect are some students can not read about word math correctly, some of students can not identify the goal of word math, the students can not retell with their own word;(2)difficulty aspect prerequisites are students can not write/identify in problem, the inability of students in transforming word math into mathematical models, and the lack of students understanding of the concept is applied, so that the student is difficult to determine the formula/strategies is used;(3)difficulties applied aspects students can not use the exact formula or occurs of missing in substitution in the formula;lack of understanding of the material prerequisites which can lead to low accuracy of students.